“FEEL THE GREEN”: HOW GREEN MARKETING STRATEGY INFLUENCES THE BUSINESS PERFORMANCE OF RESTAURANTS IN BADUNG REGENCY - Diatmika, I Putu Gede; Putra, Made Pramana; Padang, Rikky Rundu; Suciyawati, Ni Putu (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
Green marketing has become a strategic issue to improve companies' business performance in the current era of rapidly increasing industrialisation and rising environmental concerns. A business cannot focus on economic or profit orientation alone; instead, it must consider the dimensions of environmental impact and social effects. Currently, sustainable business processes are experiencing challenges from consumers who are increasingly aware of sustainability, which has encouraged companies to adopt environmentally friendly business practices. In recent decades, green marketing has emerged as a strategy that promotes sustainable products and services and encourages corporate social responsibility. In Indonesia, especially in Badung Regency, the rapid development of the restaurant industry has created a climate of intense competition in the region. Restaurant business owners must start thinking about creating a culinary industry climate that positively impacts the environment and affects long-term business continuity. Based on this. Green marketing is one area that provides a stimulus to achieve sustainability goals and provides a fundamental change in the management paradigm in terms of both marketing and business functions. This study aims to analyse the impact of green marketing and consumer behaviour on business performance in Badung, Indonesia. The research uses quantitative methods, namely a research approach that prioritises numerical data (numbers) and statistical analysis to test hypotheses. The main result reveals that green marketing positively and substantially influences a restaurant's performance. Furthermore, results show that consumer behaviour has positively and significantly mediated the impact of green marketing on business performance. This mechanism provides deeper insight into how green marketing improves sustainable business performance. Keywords: Business Performance; Consumer Behaviour; Green Marketing; Restaurant; Badung JEL Classification: D13, I31, J22, K31